Colored Petri nets-based control and experimental validation on three-tank system level control. Issue 1 (2nd January 2023) - Brezovan, Marius; Precup, Radu-Emil; Selişteanu, Dan; Stănescu, Liana
ABSTRACT: An approach to the Colored Petri Nets (CPN)-based control is proposed in this paper. CPN are used for modeling the dynamics of both the controller and the controlled process in the control system structure. The mathematical model of the controlled process is discretized in order to use CPN in modeling the controlled process and the control system as well. The proposed controller implements a Moore automaton. The theoretical aspects of the controller design are presented in the paper, as well as aspects of the system controllability. The level control of three-tank systems is considered to validate the proposed controller. Extensive simulations are performed using the CPN Tools tool and experimental results on laboratory equipment are included.